Self Concept Siswa SD dalam Belajar Matematika - Dewi, Eva Septiana; Fiantika, Feny Rita; Prayogo, Prayogo (Universitas Muhammadiyah Magelang, 2026)
Self concept is a representation of how we perceive ourselves, how others view us, and how we aspire to be. This study aims to identify the self-concept of students in learning mathematics. The research employs a qualitative approach with a descriptive-exploratory design. The subjects are Year V-A students at SDN Kebonagung 1 Sukodono. Data is collected through student scores, observations, interviews, and documentation. The data analysis technique involves data reduction, data presentation, and drawing conclusions. The findings reveal that subjects with a high self-concept demonstrate strong self confidence, both in moral and ethical aspects as well as social and personal dimensions. They believe in their abilities, can collaborate effectively, and exhibit perseverance when solving mathematical problems. Conversely, subjects with a moderate self concept possess reasonably good self confidence but lack certainty regarding their work outcomes. Nonetheless, they are still able to interact and contribute within a group setting. Meanwhile, subjects with a low self concept tend to have weak self confidence, struggle with self regulation when solving mathematical problems, and display difficulty interacting and accepting criticism. Consequently, it can be concluded that the higher a student's self-concept, the better their ability to solve mathematical problems.